(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
E-governance is simply defined as the utilization of internet technology as a platform for sharing information, facilitating services and making interactions with citizens, businesses and other sectors of government. E-governance facilitates sound strategy to empower the overall governance. It does not only enhance transparency, efficiency and accountability of government processes, but also provide sustainable and comprehensive growth. It also facilitates mechanism of direct delivery of customer services to the marginal section of the society in the remotest areas, without involving the intermediaries. This paper basically deals with the various strategies involved in facilitating e-governance to different government sectors. The first segment begins with the introduction to e-governance and then there is a description of various strategies involved in establishing e-governance in India. At the end a conclusion is made to describe the future perspectives.